Occupational stress: an analysis of the causes - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Ahmad, Muhamad Hassan; Kasi, Arun (USA Passion Development Sdn Bhd, 2018)
Occupational stress may have an impact on the effectiveness of an organisation. Excessive workload or demand, stressful deadlines, long working hours, insufficient number of staff, lack of support from co-workers and supervisors, annoying co-workers, unsatisfied customers, and hazardous working conditions, among others are some of the underlying causes of occupational stress. Job uncertainty due to impending retrenchment, restructuring or management changes and hostile work environment could also give rise to occupational stress. Occupational stress often results in high dissatisfaction among the employees in terms of job mobility, burnout and poor work performance and less effective interpersonal relations at work. Excessive or unmanageable demands, insufficient support from co-workers and unsatisfactory working conditions may affect staff-motivation and productiveness. Longterm stress or traumatic events at work may have affect the workers physically and psychologically. In light of the above, this paper seeks to deliberate on the causes of occupational stress with reference to unmanageable workload,job insecurity, sexual harassment, workplace discrimination and employer’s unlawful conduct.